2014
DOI: 10.1016/j.jdeveco.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Out-migration, wealth constraints, and the quality of local amenities

Abstract: Using a simple theoretical model, we show that the level of migration costs relative to wealth determines the form of the relation between income and migration intentions, which can be monotonically decreasing, increasing, or inverse U-shaped. Using unique individual level data, covering three geographic regions-sub-Saharan Africa, Asia, and Latin America-we show that migration intentions do indeed respond to individual wealth, and that the patterns differ across the country groups studied in a manner compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
162
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(189 citation statements)
references
References 29 publications
14
162
1
Order By: Relevance
“…These results suggest that policy interventions such as cash transfer programs and expansions of flood protection could give households more options to respond to future environmental shocks associated with climate change. Regarding contemporary labor migration, our results contribute to a literature documenting that migration is costly and that even temporary moves can be undermined by a lack of resources (Bryan et al, 2014; Dustmann & Okatenko 2014), in this case by short-term flooding and by medium-term wet and dry precipitation shocks. Given this context, policies that buffer against shocks (e.g., crop insurance) or reduce barriers to migration (e.g., land registration) should be considered in order to improve access to livelihood-enhancing temporary migration.…”
Section: Discussionsupporting
confidence: 57%
“…These results suggest that policy interventions such as cash transfer programs and expansions of flood protection could give households more options to respond to future environmental shocks associated with climate change. Regarding contemporary labor migration, our results contribute to a literature documenting that migration is costly and that even temporary moves can be undermined by a lack of resources (Bryan et al, 2014; Dustmann & Okatenko 2014), in this case by short-term flooding and by medium-term wet and dry precipitation shocks. Given this context, policies that buffer against shocks (e.g., crop insurance) or reduce barriers to migration (e.g., land registration) should be considered in order to improve access to livelihood-enhancing temporary migration.…”
Section: Discussionsupporting
confidence: 57%
“…Recent papers use both individual and aggregate data. Most individual-level studies show that financial constraints do matter for migration (see Dustmann and Okatenko, 2014 on sub-Saharan Africa and Asia regions, Mendola, 2008;Sharma andZaman, 2013 on Bangladesh, Beam et al, forthcoming andMcDonald andValenzuela, 2012 on the Philippines, and Friebel and Guriev, 2005 on Russia). Some other studies (e.g., Beegle et al, 2011 on Tanzania andAbramitzky et al, 2013 on Norway) find no significant effects.…”
mentioning
confidence: 99%
“…Using individual-level data allows us to relax the restriction. Previous literature has also found that distance, cultural similarities (Belot and Hatton, 2012), language barriers, immigration policies (Mayda, 2010), wealth level (Dustmann and Okatenko, 2014) and migrants' network (McKenzie and Rapoport, 2010;Pedersen et al, 2008;Piotrowski, 2006) are important factors affecting the likelihood of migration. Ability to finance the cost of migration also affect migration likelihood and Ilahi and Jafarey (1999) find evidence of extended family taking out loans to finance the migration cost of the migrants in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%